Tectonic Stress Distribution in the Song Tranh 2 Hydropower Reservoir: Implication for Induced Earthquake - Hoai, Luong Thi Thu; Nguyen Ha Vu, Pham; Dinh Nguyen, Nguyen; Thi Phuong Thao, Hoang; Van Vuong, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 37 No 2, 2021)
The Song Tranh 2 hydropower reservoir was built in Tra My area, Quang Nam province, composing magmatic and high-grade metamorphic rocks of the northern part of the Kon Tum massif. Since the reservoir was put into operation, induced earthquakes have occurred in the Song Tranh 2 hydropower reservoir and its vicinity. Tectonically, the northwest-southeast to east-west striking faults developed strongly. Detailed analysis of slickensides and attitude of faults occurring in the studied area have shown that the northwest-southeast striking faults are reactivated as dextral ones during the Pliocene-Quaternary up to the present day. Based on the geometric distribution of the fault network, kinematic characteristics, and the youngest tectonic stress regime, we computed the distribution of tectonic stress in the studied area. Computation results show two positive anomalies of stress directly related to the northwest-southeast faults numbered 2, 10, 11a, 11b and sub-latitude striking fault numbered 1. These faults run in line with the local river channels and are likely to reactivate and generate induced earthquakes.